Advancements in green materials for chemical enhanced oil recovery: A review - Jamil F. El-Masry; Elsa Maalouf; Azza H. Abbas; Kamel F. Bou-Hamdan (Petroleum, 2025)
Chemical enhanced oil recovery (CEOR) is well known for its success in recovering the trapped oil in reservoirs after waterflooding operations. In CEOR, synthetic chemicals are utilized to increase the capillary number or modify the mobility ratio of reservoirs; however, they are expensive and are associated with environmental concerns. Hence, the rise in environmental awareness paved the way for environmentally friendly and cheaper alternatives, such as green products, to replace synthetic chemicals. This paper comprehensively reviews recent studies on applying green products in CEOR. It also includes comparisons between the performance of several green products and their synthetic counterparts in CEOR. Moreover, limitations, cost, and environmental footprints are analyzed. Finally, the displacement efficiency of green chemicals and pertinent challenges in the field are highlighted. While the utilization of some natural materials in EOR still has an environmental impact, they constitute a safer option than synthetic chemicals. Furthermore, green materials are more affordable than synthetic chemicals that are commonly utilized, making them a financially viable option for EOR. An up-to-date overview is urgently needed due to the growth of natural chemical utilization in oil and gas applications. Promoting sustainable alternatives is essential to addressing the rise in global environmental concerns.